Genetics, diagnosis, management and future directions of research of phaeochromocytoma and paraganglioma: a position statement and consensus of the Working Group on Endocrine Hypertension of the European Society of Hypertension. Issue 8 (August 2020) - Lenders, Jacques W.M.; Kerstens, Michiel N.; Amar, Laurence; Prejbisz, Aleksander; Robledo, Mercedes; Taieb, David; Pacak, Karel; Crona, Joakim; Zelinka, Tomáš; Mannelli, Massimo; Deutschbein, Timo; Timmers, Henri J.L.M.; et al.
Abstract : N/A: Phaeochromocytoma and paraganglioma (PPGL) are chromaffin cell tumours that require timely diagnosis because of their potentially serious cardiovascular and sometimes life- threatening sequelae. Tremendous progress in biochemical testing, imaging, genetics and pathophysiological understanding of the tumours has far-reaching implications for physicians dealing with hypertension and more importantly affected patients. Because hypertension is a classical clinical clue for PPGL, physicians involved in hypertension care are those who are often the first to consider this diagnosis. However, there have been profound changes in how PPGLs are discovered; this is often now based on incidental findings of adrenal or other masses during imaging and increasingly during surveillance based on rapidly emerging new hereditary causes of PPGL. We therefore address the relevant genetic causes of PPGLs and outline how genetic testing can be incorporated within clinical care. In addition to conventional imaging (computed tomography, MRI), new functional imaging approaches are evaluated. The novel knowledge of genotype-phenotype relationships, linking distinct genetic causes of disease to clinical behaviour and biochemical phenotype, provides the rationale for patient-tailored strategies for diagnosis, follow-up and surveillance. Most appropriate preoperative evaluation and preparation of patients are reviewed, as is minimally invasive surgery. Finally, we discuss risk factors for developing metastatic disease and how they may facilitate personalised follow-up. Experts from the European Society of Hypertension have prepared this position document that summarizes the current knowledge in epidemiology, genetics, diagnosis, treatment and surveillance of PPGL. Abstract : Supplemental Digital Content is available in the text